Faktor Penentu Loyalitas Pasien Terhadap Layanan Rawat Inap di RSUD Dr. RM. Djoelham Binjai - Eric Winarno; Chintami Octavia (Jurnal Kesehatan Amanah, 2024)
Inpatient services are a form of healthcare provided by hospitals, where patients receive intensive care in specialized facilities. These services encompass integrated medical and non-medical aspects. This study aims to analyze the factors correlated with patients' decisions to reselect inpatient services at Dr. RM. Djoelham Regional General Hospital, Binjai in 2024. The research employs a quantitative approach with a cross-sectional design, involving 871 inpatients from January to March 2024. A sample of 90 patients was selected using purposive sampling. Data analysis was conducted univariately and bivariately using the chi-square test The results revealed significant relationships between several factors and patients' decisions to reuse inpatient services, namely service quality (p = 0.000), healthcare facilities (p = 0.027), and customer loyalty (p = 0.013). It is concluded that these factors play an important role in patient decisions. To enhance patient satisfaction and loyalty, the hospital is advised to focus on maintaining and improving facilities, as the availability and quality of facilities significantly affect patient satisfaction. Continuous service improvement can support the hospital's development in providing optimal care. This translation maintains the technical accuracy of the original text, including the proper representation of the hospital's name and the statistical terminology used in the study